The impact of digital transformation on low-carbon development of manufacturing - Lyu, Yanfang; Zhang, Leifeng; Wang, Dong (Frontiers in Environmental Science, 2023)
Manufacturing is the backbone of China's national economy, and its low-carbon development is essential for achieving the “dual-carbon goals”. This paper uses the matching data of China Industrial Economics Database, China Emission Accounts and Datasets (CEADs) and China's multi-regional input-output table to measure the low-carbon development level and digital transformation degree of 17 manufacturing industries in 30 provinces of China from 2012 to 2018. On this basis, high-dimensional fixed effect model and panel threshold model are constructed to investigate the effect of digital transformation on the low-carbon development of the manufacturing industry. The results indicate that: (1) During the study period, China's manufacturing industry showed an upward trend in terms of low-carbon development level and digital transformation, but there were significant regional and industrial disparities. (2) Digital transformation can significantly promote the low-carbon development of manufacturing industry, which is still valid in the robustness test. (3) For sub-indicators, digital industrialization has the most obvious effect on the low-carbon development of manufacturing industry, and the improvement of digital development environment also has a positive impact on low-carbon development. (4) The heterogeneity analysis indicate that digital transformation has a greater impact on promoting low-carbon development of manufacturing in underdeveloped regions, and the positive effect is obvious in medium-low-energy-consuming industries, but not in high-energy-consuming industries. (5) The threshold model results show that the impact of digital transformation on low-carbon development has an inverted U-shaped relationship of rising first and then declining. This paper provides empirical evidence for the environmental impact of digital transformation, and offers a scientific basis for relevant departments to formulate low-carbon development policies from the perspective of digital transformation.